Analysis of Teaching Strategies in Reading Comprehension to Seventh Grade Students in Junior High School: Analisis Strategi Mengajar Dalam Pemahaman Membaca Pada Siswa Kelas Tujuh di Sekolah Menengah Pertama - Mochammad Teguh Ade Pranata; Dian Novita (Academia Open, 2021)
Reading comprehension is a person's ability to know and understand the meaning contained in a reading text. Teaching strategy is a teacher’s scheme in teaching and learning process to achieve a aim which have plan. The study aimed to explore teaching strategies and implementation in reading comprehension in seventh grade students at SMPN 2 Jabon Sidoarjo. This research method is qualitative research. The subject of this research is an English teacher at SMPN 2 Jabon Sidoarjo. The research instrument is a checklist of observations and interviews. The results of the study found that there were three strategies used by the teacher, Text-Based Instruction, Finding the meaning (scaffolding) and exercise (online learning). With Text-Based Instruction the teacher provides several steps to improve students' reading comprehension skills, Finding the meaning (scaffolding) strategies to help students develop ideas that can be read by students, and exercises (online learning) to hone students' skills while studying at home.